Analyse de l'utilisation asymétrique du pouvoir dans les conflits miniers au Pérou - Céline Cardinaël; Olivier Petit (VertigO)
This article deals with mining conflicts in Peru and mobilizes a Political Ecology approach, focusing on the importance of power asymmetries. After presenting the methodological and theoretical framework of our study, we present a legal and institutional overview of the relationships between the Peruvian state and mining issues. We insist on the historical and territorial dimensions which help to understand why the mining issue exacerbates power asymmetries, already important in Peru. The article then focuses on the Conga case study, to illustrate how the various elements identified at the national level are also taking concrete form on the ground, in this emblematic case. We then discuss the main lessons derived from this analytical framework and from the Conga case study, compared with other socio-environmental conflicts in Peru. The paper concludes with the arguments in favor of a post-extractivist solution and its feasibility conditions, given the persistence of a power asymmetry.